2018
DOI: 10.1002/mnfr.201800243
|View full text |Cite
|
Sign up to set email alerts
|

A Moderate Interleukin‐6 Reduction, Not a Moderate Weight Reduction, Improves the Serum Iron Status in Diet‐Induced Weight Loss with Fish Oil Supplementation

Abstract: Fish oil is ineffective as an adjunct for weight or fat loss but has beneficial effects on preserving the lean body mass. A significant improvement in the iron status is only observed in those with moderate loss of serum IL-6 supplemented with fish oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In total, 879 subjects who were OW or obese (mean BMI: 31.8 ± 4.17 kg/m 2 , 82% females) were included, of which 660 were adults (mean BMI: 32.9 ± 4.23 kg/m 2 ) and 219 were children and adolescents (mean BMI: 25.2 ± 3.83 kg/m 2 ). Eight studies 15,21,22,24,33–36 (57.1%) were RCTs and six studies 14,16,17,19,20,23 (42.9%) were longitudinal studies. In adults, 10 studies (10/11) employed hypocaloric diet‐induced weight loss, with the exception of one study that used exercise as a stand‐alone weight‐loss programme 36 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 879 subjects who were OW or obese (mean BMI: 31.8 ± 4.17 kg/m 2 , 82% females) were included, of which 660 were adults (mean BMI: 32.9 ± 4.23 kg/m 2 ) and 219 were children and adolescents (mean BMI: 25.2 ± 3.83 kg/m 2 ). Eight studies 15,21,22,24,33–36 (57.1%) were RCTs and six studies 14,16,17,19,20,23 (42.9%) were longitudinal studies. In adults, 10 studies (10/11) employed hypocaloric diet‐induced weight loss, with the exception of one study that used exercise as a stand‐alone weight‐loss programme 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies reported baseline and endpoint values of serum ferritin (14/14), serum iron (12/14), %TS (11/14), Hb (11/14), BW (13/14) and BMI (11/14). However, only four studies reported serum hepcidin (4/14) and IL‐6 (4/14) concentrations 15–17,24 . The range of the intervention duration was 1.5–24 months (adults: 1.5 to 24 months, children: 6 to 12 months), and the ranges of reductions in BW and BMI were −14.9 to 4.7 kg (adults: −14.9 to −0.15 kg, children: −3.8 to 4.7 kg) and −4.5 to 0.4 kg/m 2 (adults: −4.5 to −0.51 kg/m 2 , children: −3.4 to 0.4 kg/m 2 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations